2004
DOI: 10.1002/macp.200400253
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Interpolymer Complex between Hydroxypropyl Cellulose and Maleic Acid‐Styrene Copolymer, 1

Abstract: Summary: The hydrogen bonding‐interpolymer association of hydroxypropyl cellulose (HPC) with maleic acid‐styrene (MAc‐S) copolymer has been investigated in dilute aqueous solution by viscometry, turbidimetry and potentiometry. At a mixing ratio between MAc‐S and HPC of 10:90, the solution exhibits a phase separation upon heating, while for other mixing ratio no phase separation could be detected. The stability of the interpolymer complex (IPC) increases as the temperature rises. The stoichiometry of the IPC, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…DLS investigation confirmed the possibility of generalizing this approach to fabricate nanoparticles from HPC and carboxyl-ended surfactants. Besides, because many other water-soluble polysaccharides can also complex with carboxyl-containing macromolecules or surfactants, [7,19,20,32] this approach shows considerable potential in preparing nanoparticles from various water-soluble polysaccharides and carboxyl-ended surfactants.…”
Section: Self-assembly Of Hpc With Other Carboxylended Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…DLS investigation confirmed the possibility of generalizing this approach to fabricate nanoparticles from HPC and carboxyl-ended surfactants. Besides, because many other water-soluble polysaccharides can also complex with carboxyl-containing macromolecules or surfactants, [7,19,20,32] this approach shows considerable potential in preparing nanoparticles from various water-soluble polysaccharides and carboxyl-ended surfactants.…”
Section: Self-assembly Of Hpc With Other Carboxylended Surfactantsmentioning
confidence: 99%
“…It has been reported that the self-assembly of a pair of polymers having hydrogen bonding interaction could result in non-covalent connected micelles (NCCM), [6,18] and like many other kinds of cellulose ether, HPC can interact with carboxyl groups via hydrogen bonding. [7,[19][20][21] Hence, we studied the self-assembly behavior of HPC with one kind of carboxyl-ended LMS, decanoic acid (Deac) in solution. In order to demonstrate the ubiquity of preparing nanoparticles by this approach, another carboxyl-ended LMS, pentadecylfluorooctanoic acid (PDFOA), was chosen to study the self-assembly of HPC with other carboxyl-ended LMS.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work we showed that HPC and MAcalt-S copolymer form interpolymeric complexes, IPC via hydrogen bonding interactions between the oxygen of the ether groups of HPC and the OHgroups of the carboxyl groups of MAc-alt-S [17,18], IPC stabilized by hydrophobic interactions between the isopropyl side chain of HPC and the styrene groups of MAc-alt-S [19]. The stoichiometry of the interpolymeric complex was estimated to be HPC/MAc-alt-S = 40:60 [w/w] independent of the total polymer concentration in the system, c pol .…”
Section: Introductionmentioning
confidence: 99%
“…The maximum concentration of the precipitate in the gel phase is also reached at a mixing ratio between HPC and MAcalt-S of 40/60 that corresponds to the stoichiometry of the complex. At pH lower than 4.5 the HPC/ MAc-alt-S, IPC becomes water-insoluble [18]. It is well known from membrane science that the morphology and therefore the permeability and transport characteristics highly depend on the way of preparation [20].…”
Section: Introductionmentioning
confidence: 99%
“…[12] In one of our recent papers, we discussed the capability of hydroxypropylcellulose to form an IPC with MAc-S in aqueous dilute solution and evaluated the thermodynamic function of the complexation process. [13] The interest in IPCs formed between a synthetic polymer and a macromolecule of biological origin has increased due Summary: The formation of interpolymer complexes (IPCs) between hydroxypropylcellulose (HPC) and copolymers of maleic acid with vinyl acetate (MAc-VA), acrylic acid (MAc-AA) and styrene (MAc-S) in aqueous solution has been investigated by turbidimetry, viscometry and fluorescence measurements. The viscosity data indicated a compact structure for the IPCs between HPC and maleic acid copolymers.…”
Section: Introductionmentioning
confidence: 99%